ORGANIC WASTE MANAGEMENT STRATEGIES USING MAGOOT IN REALISING GO GREEN PRISON AT THE NARCOTICS CORRECTIONAL INSTITUTION CLASS IIA JAKARTA - Rahim, Zaki; Santoso, Iman (Universitas Nusa Cendana, 2025)
Corrections uses a social reintegration approach as the basis of its work, with an emphasis on the process of recovery and integration of prisoners with society after they have committed a criminal offence. This concept regards crime as a conflict between the offender and society, and the main goal of corrections is to restore offenders so that they can reintegrate into society in a positive way. The purpose of this study is to determine the organic waste management strategy using BSF maggot in realising go green prison at the Class IIA Jakarta Narcotics Prison. The author chose to use descriptive qualitative research design as a research method. The results of this study based on SWOT analysis that the implementation of Go Green Prison in Class IIA Jakarta Narcotics Prison is realised by the implementation of waste management into maggot feed. However, in the implementation there are several obstacles, one of which is the weather conditions that affect the process of implementing the programme